Receptor-induced thiolate couples Env activation to retrovirus fusion and infection. - Jason G Smith (Public Library of Science (PLoS), 2007)
According to current models of retrovirus infection, receptor binding to the surface subunit (SU) of the envelope glycoprotein (Env) triggers a conformational change in the transmembrane subunit (TM) that mediates virus fusion to cell membranes. To understand how this occurs, we investigated the role of the receptor Tva in avian leukosis virus-A (ALV-A) infection. We find that Tva binding induced the formation of a reactive thiolate on Cys38 (Cys38-S- in SU. Both chemical and genetic inactivation of Cys38-S- completely abrogated ALV fusion and infection. Remarkably, Cys38-S- does not mediate isomerization of the SU-TM disulfide bond and is not required for Tva-induced activation of TM, including pre-hairpin association with membranes and low pH assembly of helical bundles. These findings indicate that, contrary to current models, receptor activation of TM is not sufficient for ALV fusion and infection and that formation of a reactive thiolate is an additional receptor-dependent step.